(untitled) (Sciences & Technology. A, exactes sciences, 2016)
The present study investigated the adsorption behavior of Methylene Blue dye from aqueous solution onto Activated carbon, Bentonite, Kaolin, Animal charcoal and Wood charcoal. To assess the adsorptive effectiveness of these natural adsorbents and their comparative adsorption capacities, initial dye concentration and contact time, the effect of adsorbent dosage and solution pH were studied. Activated carbon and Bentonite were top ranking and exhibit outstanding adsorption capacities followed by Kaolin and Animal charcoal with similar behavior but less effective. Finally, Wood charcoal showed the poorest adsorption capacity. Generally, Langmuir adsorption isotherm model has the best fit compared to Freundlich model. The study of adsorption kinetics was well described by the pseudo-second order model.